Early Childhood Caries in 4- to 5-Year-Old Children in Erzurum, Turkey - Şengül, Fatih; Urvasızoğlu, Gelengül; Derelioǧlu, Sera; Seddik, Tarek; Çelikel, Periş; Baş, Aybike (Frontiers in Public Health, 2021)
Introduction: Early childhood caries is tooth decay seen in children under 72 months old. It is associated with multiple predisposing factors and has a negative impact on quality of life. In this study, our aim was to assess the oral health conditions and prevalence of early childhood caries (ECC) in children in the city of Erzurum, Turkey. Materials and Methods: This cross-sectional epidemiological study was conducted in Atatürk University, Faculty of Dentistry, Pediatric Dentistry Department/Erzurum-Turkey, in the 2015–2016 academic year. A total of 1,156 children (588 girls and 568 boys), with mean age of 4.9 ± 0.3 years (min 4, max 5) were included in the study. Restorative index (RI), deft, significant caries index (SiC), SiC10, treatment needs, number of lost primary teeth per 100 children, care index, and prevalence of carious primary teeth were evaluated. Data were analyzed by Chi-square test and Mann–Whitney U test (p < 0.05). Results: A total of 73.3% prevalence of ECC was observed in preschool children with a mean deft score of 3.9±4 and an increase in ECC with age. RI was 2.2%, SiC was 8.5, SiC10 was 12.3, caries treatment needs was 93.5%, care index was 2.1%, and number of lost primary teeth per 100 children was 0.9 tooth. Conclusion: High level of ECC indicates the necessity of starting an oral health education program for mothers and dental screening of children, and the demand for improving oral and dental services.